Pengaruh Perawatan Bayi Lekat Terhadap Pencapaian Pertumbuhan Bayi Berat Lahir Rendah Di RS DR. Sardjito Yogyakarta - Lely Lusmilasari, Achmad Surjono dan Ekawaty Lutfia Haksari (Berita Kedokteran Masyarakat (BKM), 2004)
Background: In conventional care method, a low birth weight infants (LBWi) needs an incubator or even radiant heater to prevent hypothermic and improves its general condition, but both devices are so costly that a new way of nursing called kangaroo mother care (KMC) is developed. Objective: To determine the influence of KMC and the difference in growth achievement between LBWi nursed with KMC and the others with conventional method up to the age of three months. Methods: The study was a quasi experiment with Non-Equivalent Control Group design, carried out at DR Sardjito Hospital Yogyakarta. The sample consists of pairs of Mother-LBWi, chosen using consecutive sampling were divided into two groups of treatment group and control group. Data analysis was conducted by using SPSS program. Results: The mean z score of weight for age was – 1,193 ± 0,600 (treatment group) and – 1,308 ± 0,586 (control group), (mean difference: 0, 1159; CI 95% = –0.123 to +0.355; p=0,339). The mean z score of height for age was – 2, 20 ± 1,158 (treatment group) and-2, 52 ± 0,956 (control group), (mean difference: 0, 325; CI 95%= –0,103 to +0,753; p=0,136). The mean head circumference for age was 39, 19 ± 3, 04 (treatment group) and 38, 54 ± 1.95 (control group), (mean difference of 0, 65; CI 95% =-1.381 to +1.685; P=0.213). Conclusion: The mean z score of weight for age and height for age, head circumference for age in treatment group were higher than that control group, there were no significant differences between the two groups. Keywords: Kangaroo Mother Care; low birth weight infants (LBWi); Growth